Pengembangan Media Pembelajaran Berbasis Scratch pada Pokok Bahasan Alat Optik (UPEJ Unnes Physics Education Journal, 2019)
This study aims to develop Scratch-based learning media on the subject of optical tools and measure the properness of learning media. Learning media developed with 4D development model by Thiagarajan. The research subjects were Scratch-based learning media which tested for their properness. The properness test process was carried out by using a questionnaire consist of validating questionnaires of visual communication design aspect, software engineering aspects, material substance aspects, quality test questionnaires of learning media by the teacher, and responses questionnaires of student. The questionnaire respondents were expert lecturers for each aspect, physics teachers, and high school students in XI MIPA grade. Questionnaire data were analyzed by descriptive statistical analysis and average value of statistics described according to the properness criteria of learning media. The results of the properness of learning media on the visual communication design aspects obtained a percentage of 94% with very proper categories, aspects of software engineering obtained a percentage of 83% with very proper categories, material substance aspects obtained 70% with a proper category, percentage of learning media quality test 91 % with a very proper category, and students responses obtained a percentage of 79.84% with a proper category. Based on data analysis, it can be concluded that Scratch-based learning media on the subject of optical tool is proper to be used as a medium for physics learning in the learning process at school.